My-Peer Toolkit 1.0: Guidelines for planning, implementing and evaluating peer-based youth programs. - Hallett, Jonathan; Lobo, Roanna; Brown, Graham; Hildebrand, Janina; McManus, Alexandra; Maycock, Bruce; Burns, Sharyn (WA Centre for Health Promotion Research, Curtin University, 2010)
This toolkit is a resource aimed at supporting agencies to implement and evaluate peer-based programs for young people using good practice guidelines.